(untitled) (Review of Croatian History, 2022)
The paper explains the distribution, based on sources and historiographical works, of settlements on the Vérvár and Otok estate in the ​​Vukovo County in Hungarian-Croatian Kingdom in the Late Middle Ages. The central part of the paper is the analysis of medieval documents with lists of settlements from 1437, 1446 and 1476. A brief overview of the ownership of the estate was made and the issue of the Selna estate becoming property of the Otok estate was presented. According to the lists of settlements and the years stated in them, geographical maps of the estate were made.